Growth and Obesity Among Older Single Ventricle Patients Presenting for Fontan Conversion. (October 2015) - Freud, Lindsay R.; Webster, Gregory; Costello, John M.; Tsao, Sabrina; Rychlik, Karen; Backer, Carl L.; Deal, Barbara J.
Introduction: Long-term growth outcomes and the prevalence of obesity among older single ventricle (SV) patients have not been well characterized. We investigated these parameters, as well as the impact of obesity on survival, in an older cohort of SV patients presenting for Fontan conversion. Methods: We analyzed preoperative height, weight, and body mass index (BMI) of patients who underwent Fontan conversion. Overweight and obese were defined as BMI ≥85 percentile and ≥95 percentile for patients <20 years and BMI 25 to 30 kg/m 2 and ≥30 kg/m 2 for patients ≥20 years, respectively. Postoperative transplant-free survival was assessed among obese, overweight, and normal weight patients. Results: We evaluated 139 patients presenting for Fontan conversion at a median age of 23.2 years. Patients had shorter stature compared to the normal population (mean Z score −0.6, P < .001). Younger patients had lower BMI compared to the normal population (<20 years: mean Z score −0.5, P = .02), while older patients had elevated BMI (≥20 years: mean Z score +0.4, P < .001). The mean BMI among older patients approached overweight at 24.6 kg/m 2 . The prevalence of obesity increased with advancing age, with 36% overweight and 14% obese at >30 years. At a median of 8.2 years following Fontan conversion, obesity and overweight status were not associated with transplant-free survival. Conclusion: Older SV patients presenting for Fontan conversion had shorter stature compared to the normal population as well as a high prevalence of overweight and obesity. Although there was no relationship between weight status and early postoperative survival, further investigation of long-term outcomes is warranted.